Speculators in conflict : the Adventurers and the Wars of the Three Kingdoms, 1642 - 1660 - Brown, David (Trinity College (Dublin, Ireland). Department of History, 2016)
This study reveals how the actions of an extraordinary group of skilled and innovative individuals, less than twenty in number, developed and maintained a stable system of state finance in highly challenging times. They profited enormously from their efforts and left behind them both an early form of centralised English fiscal state and the framework upon which England's overseas empire was built. The Adventure for Irish Land of February 1642 was a speculation in the conquest of Ireland, a reaction to the Catholic rebellion of October 1641. Money contributed towards an army to conquer the Catholic rebels would be repaid in land. The Adventurers for Irish Land were the individuals who subscribed money into this scheme, despite having no prior interest in Ireland. Their significance has never been fully investigated.
Keywords: Histories & Humanities, Ph.D.; PhD Trinity College Dublin, 2016